The imperial trace recent Russian cinema - Condee, Nancy (Oxford University Press, 2009)
In this study Condee argues that we cannot make sense of contemporary Russian culture without accounting for its imperial legacy. She turns to the instance of contemporary cinema to focus this line of inquiry. This book centres on the work of Russia's internationally ranked auteurs of the late Soviet and post-Soviet period.